Teaching China to the world: Evaluating the CAASK model for international student education - Fei, Yanhong; Qi, Hua (Journal of International Students, 2026)
As a compulsory course for international students in China, the Overview of China course helps them understand and adapt to different aspects of China through introductions. However, current research lacks enough focus on its teaching models. This study develops the CAASK teaching model, based on Fantini’s paradigm and the course’s actual situation, to optimize teaching effects. This model comprises both theoretical and practical dimensions: the theoretical dimension includes five concepts, which are cross-cultural awareness, attitude, comparison, knowledge, and skills; and the practical dimension encompasses four methods, which are in-class discussion, group presentation, lecture, and independent learning, as well as three stages, which are preclass self-study, in-class interaction, and postclass consolidation. Over the course of one academic year, this study verified the model’s effects through classroom observations and semistructured interviews in undergraduate, postgraduate, and PhD classes. The cognitive, attitudinal, and behavioral effects of this model were analyzed, all confirming the CAASK model’s usefulness.